Research of application possibility of magnetometric method for control of mechanical stresses of ship hull - Завальнюк, Ольга Петровна (Technology audit and production reserves, 2015)
The possibility of using magnetometric method to control the mechanical stresses of the hull is investigated in the article. The magnetic stray field of the hull as the ferromagnetic object control, created a uniform field of the Earth, is calculated for this purpose. The hull is represented as the totality of the surface field sources. It is compiled the Fredholm equation of the 2nd kind, which was reduced to a system of linear algebraic equations by approximating the surface of the object control set of elementary areas of rectangular shape. The average value of the normal component of the magnetization on each side of the platform has enabled to determine the magnetic field outside of the hull. Results of the study of the magnetic stray field of the hull showed that the voltage measuring range is sufficient to measure the modern magnetic modulation converters - ferroprobes. It is shown that this method is an effective method to control the mechanical stresses of the hull, which prevents exceeding the permissible stresses in the supporting structures of the ship, which could lead to the destruction of the hull.